Development of process conditions to optimize the extraction of bio-disinfectant from Neem Leaf (Azadirachta Indica) - Jamal, Parveen; Al-Mamun, Abdullah; Wan Chik, Wan Dalila; Zainuddin, Zaki; Mirghani, Mohamed Elwathig Saeed (American-Eurasian Network for Scientific Information, 2012)
Central composite design (CCD) under Response surface methodology (RSM) was used in the present study to optimize the extraction parameters for assessing, maximum yield of bio-disinfectant content from Neem leaves extract (NLE). The range of the independent variables, namely solid-solvents ratio (0.05-0.1 w/v), extraction time (1-5 hrs), agitation speed (50-250 rpm) and extraction temperature (35-60 °C) were identified by a first set of four factors and five levels experiments. The optimum conditions for extraction of bio-disinfectant content from NLE were found to be at 75% ethanol with solid solvent ratio 0.067, extraction time 3 hrs, agitation speed 150 rpm and extraction temperature 60 °C. Under these optimized conditions, the maximum activity for bio-disinfectant yield was obtained, which showed 5.57 cm2 inhibition zones for anti-microbial assay. The experimental result was in close agreement with predicted values, thus indicating the suitability of the models developed and the success of RSM in optimizing the extraction conditions.